Estimating flow rate in gauged and ungauged station in Kuantan river basin using clark method in HEC-HMS - Nuramirah, Sharif (2018)
Estimating flow rate by using hydrologic simulation engaging computer model is at the cutting edge of ways to boost the understanding and provide further reliable outcomes. Nowadays, due to its undeniable contribution, it has become indispensable tools to design any ecologically sustainable water management approaches. US Army Corps of Engineers has taken an initiative to develop a stable and dependent model, HEC-HMS that could be used for many hydrological simulations. The value of parameter needed in order to complete the simulation basically depends on the method chosen for loss, transform and base flow. Reliable and precise data inputs needed to check suitability of the model for the study location area and the purpose of the research if there is no any calibrate and validate process. However, in this study, the model parameters were changed and the model calibration was performed separately for the three selected methods, the Soil Conservation Service Curve Number loss method, the Constant Monthly base flow and the Clark Unit Hydrograph for transform method to determine the most suitable simulation and to obtain the highest peak discharge for every sub basin in Kuantan River Basin. The step taken after obtaining the calibrated model is to run the validation process to validate the hydrologic model and ensure it can be used for other set of rainfall and flow data in that area for different event of rainstorms. For every flow simulated for validation and calibration process, the Nash-Sutcliffe index (NSE) was used as a criterion to compare the outcomes between observed and simulated hydrograph. The acceptable model has a range of NSE in between 0.8 to 1.0. Simply saying, the closer the value of NSE to 1, the higher the similarity of the simulated and observed hydrograph. In the first process of calibration, NSE value obtained is 0.81 for the rainstorm event of 4th September 2010, this value shows that the model is well performed and good enough to be used. In order to validate the calibrated model before, validation process was done using different data set of rainfall and stream flow from calibration process. Rainstorm event of 12th October 2013 was used and the value of NSE produced is 0.91. As the chosen transformation method in this study, Clark Unit Hydrograph simulates the flows successfully and the parameter value is easy and simple to be fulfilled. Therefore, the Clark Unit Hydrograph method could be recommended as the best transformation method for the Kuantan River Basin with the SCS Curve Number as the loss method. As there are plenty of ungauged rivers located in the Kuantan River Basin, this approach can reliably be applied in order to simulate river flows in the other areas with same characteristic and also the same approach of calibration and validation can be applied in other parts of the tropics.